2015
DOI: 10.3389/fncel.2015.00203
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species trigger motoneuron death in non-cell-autonomous models of ALS through activation of c-Abl signaling

Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease in which pathogenesis and death of motor neurons are triggered by non-cell-autonomous mechanisms. We showed earlier that exposing primary rat spinal cord cultures to conditioned media derived from primary mouse astrocyte conditioned media (ACM) that express human SOD1G93A (ACM-hSOD1G93A) quickly enhances Nav channel-mediated excitability and calcium influx, generates intracellular reactive oxygen species (ROS), and leads to death of moton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(93 citation statements)
references
References 113 publications
(219 reference statements)
4
89
0
Order By: Relevance
“…Recently, Rojas and colleagues demonstrated that the astroglial-conditioned media from mSOD1 model brought about mitochondrial dysfunction, ROS elevation, and Ca 2+ influx in normal glial cells, as well as neurons [60]. The ability of the conditioned media from these cultures to exert toxicity to neurons, as well as propagating pathology to glial cells, provides further proof to our own model of the propagation of pathology through the circulating fluid (ALS-CSF).…”
Section: Discussionmentioning
confidence: 90%
“…Recently, Rojas and colleagues demonstrated that the astroglial-conditioned media from mSOD1 model brought about mitochondrial dysfunction, ROS elevation, and Ca 2+ influx in normal glial cells, as well as neurons [60]. The ability of the conditioned media from these cultures to exert toxicity to neurons, as well as propagating pathology to glial cells, provides further proof to our own model of the propagation of pathology through the circulating fluid (ALS-CSF).…”
Section: Discussionmentioning
confidence: 90%
“…This occurs through p66Shc which generates H 2 O 2 that in turn, reacts with cytochrome c and induces oxidation of the mPTP and mitochondrial swelling (126). This mechanism is similar to neural degenerative diseases where induction of ROS (80, 113) contributes to motor neuron death (116). Thus, mitochondrial susceptibility to mPTP opening is a common point which triggers downstream cell destruction in both neuron and muscle cells.…”
Section: Mitochondria Permeability Transition Pore Sensitization Withmentioning
confidence: 83%
“…Controls included ACM derived from transgenic mice expressing hSOD1 WT (ACM-hWT) or non-transgenic mouse SOD1 WT (ACM-WT) astrocytes. Thus, mutant SOD1-expressing astrocytes derived from mice (Castillo et al, 2013;Di Giorgio et al, 2007;Fritz et al, 2013;Nagai et al, 2007;Rojas, Cortes, Abarzua, Dyrda, & van Zundert, 2014;Rojas et al, 2015), rats (Cassina et al, 2008;Vargas, Pehar, Cassina, Beckman, & Barbeito, 2006), and humans (Marchetto et al, 2008) cause motoneuron pathology and death. Additionally, immunohistochemical analyses at day 16 revealed reactive astrogliosis and significant loss of motoneurons in the ventral horn of the infused region.…”
Section: Funding Informationmentioning
confidence: 99%